The frequency and pattern of deranged lipid profile in patients with ischemic stroke: a retrospective study: Dyslipidemia frequency and pattern in Ischemic Stroke - Seetlani, Naresh Kumar; Kumari, Geeta; Yasmin, Farah; Hasan, Choudhary Ahmed; Hussaini, Maheen; Awan, Sana; Mubeen, Khalid Imran; Jabeen, Rakshinda; Ansari, Sadia; Siddiqui, Sarush; Aziz, Momin; Farooque, Umer (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Ischemic Stroke has been recognized as the principal cause of disability and the third leading cause of mortality worldwide. The aim of this study was to determine the frequency and pattern of dyslipidemia in patients presenting with ischemic stroke at a tertiary care hospital in Karachi, Pakistan and to evaluate the effect of demographic and clinical factors on the frequency and pattern of dyslipidemia in ischemic stroke subjects. Methods: A cross-sectional study carried on a sample size of 235 patients presenting to the out-patient clinic with paralysis, difficulty in speech, and/or loss of consciousness lasting for one hour or more. Blood samples were analyzed for total cholesterol (TC), triglycerides (TG), low-density lipoproteins (LDL), very low-density lipoproteins (VLDL) and high-density lipoproteins (HDL) by the enzymatic colorimetric methodology. These values were recorded on the pre-defined proforma by the investigators. All analysis was performed using SPSS version 23.0. Results: The average age of the patients was 50.84±11.51 years and 62.1% of them were males. The frequency of dyslipidemia was observed in more than half (n=134/235, 57.02%) of ischemic stroke patients. Regarding the dyslipidemia pattern, TC, VLDL-C and TG levels were deranged in more than 50% of the cases. The most commonly deranged values were of TC and VLDL-C, followed by TG levels. It was observed that patients with a previous history of DM (73.9%, p=0.002) and HTN (81.3%, p=0.001) had significantly higher rates of deranged lipid profiles. Lipid values were found to be more deranged in patients aged 41-50 years (p=0.002) however, no statistically significant differences were observed with respect to BMI (p=0.192) and symptoms duration (p=0.334). Conclusions: Dyslipidemia is an important risk factor for ischemic stroke, and elevated LDL-C is usually the lipid fraction implicated in the pathologic mechanism of stroke.